2023
DOI: 10.1007/s00261-023-03908-y
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging findings of intrahepatic cholangiocarcinoma arising from a biliary adenofibroma: a case report with radiological–pathological correlation

Abstract: Purpose Biliary adenofibroma is a solid microcystic epithelial neoplasm in the liver, comprising microcystic and tubuloacinar glandular tissues lined by a non-mucin secreting biliary epithelium and supported by a fibrous stroma. It is an extremely rare benign tumor with potential for malignant transformation. Herein, we report the case of a 64-year-old woman diagnosed with intrahepatic cholangiocarcinoma arising from biliary adenofibroma. Methods Imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The literature review showed that nearly 70% of BAF cases showed dysplasia/ malignancy. 2 - 22 Rare ones can show microinvasive components (<1mm). 8 The invasive front is usually seen as a pushing margin or as single-cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review showed that nearly 70% of BAF cases showed dysplasia/ malignancy. 2 - 22 Rare ones can show microinvasive components (<1mm). 8 The invasive front is usually seen as a pushing margin or as single-cell infiltration.…”
Section: Discussionmentioning
confidence: 99%